Henry's first-moon birthday - Look, Lenore; Heo, Yumi (New York : Atheneum Books for Young Readers, 2001)
A young girl helps her grandmother with preparations for the traditional Chinese celebration to welcome her new baby brother.
"An Anne Schwartz book."
Keywords: Babies -- Fiction; Grandmothers -- Fiction; Chinese Americans -- Fiction; Brothers and sisters -- Fiction; Infants -- Juvenile fiction; Juvenile materials